Pequeña Empresa: Papel de Nuevo Gerente de Marketing ESCOBITA NUEVA - Fischer, Konrad (1992)
It presents the case of a family-owned garment company whose development has responded more to the founder's desire to provide his family with a sufficiently comfortable living than to the entrepreneurial vision that would have allowed it to respond to market signals, which has led the company to lose ground to the competition. The organization of production is described; the market strategy: product, price, distribution and sales, promotion and advertising; the characteristics of the market and the competition; and the financial situation. When the founder's son takes over the business, he evaluates this situation and considers different alternatives for action: specializing in a new product line; maintaining the same product line, but with new designs; entering other markets; changing its pricing policy; its distribution and sales system, as well as promotion and advertising. The discussion of the case can be oriented towards the analysis of these options.